Pengembangan Bahan Ajar Berbasis Media Audio-Visual pada Pembelajaran Teks Anekdot untuk Siswa Kelas X Sekolah Menengah Atas Abdi Negara Binjai - Ayuningsih, Nada Sahvira; Ali, Ali; Rita, Rita (Medan Resource Center, 2025)
This study aims to develop and evaluate the feasibility of audio-visual learning media based on anecdotal text material for tenth-grade students at a senior high school. The research involved a population and sample of 31 students. Employing a Research and Development (R&D) design, the study utilized the Borg and Gall development model, which includes ten stages: (1) research and data collection, (2) planning and drafting, (3) preliminary field testing, (4) revision, (5) main field testing, (6) product refinement, (7) expanded field testing, (8) implementation testing, (9) final product refinement, and (10) dissemination and implementation. The results indicate that the developed audio-visual learning media is valid and feasible for instructional use. Media expert I gave a feasibility score of 85% (